Research on Improving Strategy of Technology Innovation Capability of Equipment Manufacturing Industry in Liaoning Province. Issue 2 (April 2021) - Fan, Xiaonan; Liu, Yang; Dai, Minghua
Abstract: With the development of the economy and the advancement of technology, major enterprises are also under heavy competitive pressure while welcoming huge opportunities for development. With the improvement of the global value chain system, all industries have realized the importance of improving technological innovation capabilities. As a traditional industrial province in our country, Liaoning Province has made some progress in technological innovation in the equipment manufacturing industry, but still has the problem of weak technological innovation capabilities. This paper takes the equipment manufacturing industry in Liaoning Province as the research object. This paper summarizes and analyzes the development status and technological innovation status of the equipment manufacturing industry in Liaoning Province. The author uses the entropy method to evaluate the technological innovation capability of the equipment manufacturing industry in Liaoning Province, and compares and analyzes it from the vertical and horizontal directions. At the same time, using the means of empirical analysis, with the help of Eviews software, a multiple linear regression model was constructed to study the factors affecting the technological innovation capability of Liaoning's equipment manufacturing industry. Finally, combined with the empirical research results, the countermeasures and suggestions for improving the technological innovation capability of Liaoning's equipment manufacturing industry are put forward.